2018
DOI: 10.1200/jop.2017.028605
|View full text |Cite
|
Sign up to set email alerts
|

Open Oncology Notes: A Qualitative Study of Oncology Patients’ Experiences Reading Their Cancer Care Notes

Abstract: Most patients thought that reading notes improved their care experiences. A small subset of patients experienced increased distress. As reading notes becomes a routine part of the patient experience, physicians might want to elicit and address concerns that arise from notes, thereby further engaging patients in their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
(13 reference statements)
3
17
0
Order By: Relevance
“…Similar emotional reactions were described in a focus group study, where two patients “thought that seeing their diagnoses in writing would be stressful enough to ‘…put me over the top.’” 30 An interview study focusing on accessing test results online also found that patients often experienced negative emotions when reading abnormal test results, and sometimes this occurred even with normal test results 47 . Lastly, a minority of oncology patients reading their notes online described this experience as emotionally difficult: “Some described a sense of sadness when reading about their cancer, even wishing that the electronic medical record would restrict their access to notes” 48 . One large‐scale survey study finds very few patients were left worried or confused after reading visit notes online 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar emotional reactions were described in a focus group study, where two patients “thought that seeing their diagnoses in writing would be stressful enough to ‘…put me over the top.’” 30 An interview study focusing on accessing test results online also found that patients often experienced negative emotions when reading abnormal test results, and sometimes this occurred even with normal test results 47 . Lastly, a minority of oncology patients reading their notes online described this experience as emotionally difficult: “Some described a sense of sadness when reading about their cancer, even wishing that the electronic medical record would restrict their access to notes” 48 . One large‐scale survey study finds very few patients were left worried or confused after reading visit notes online 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our patients, patients in this study also believed it would help them to take their medications (77%) and rated their own anticipated ability to understand the notes as 7.5 out of 10. Studies conducted after the implementation of shared notes have found that the perceived benefits and concerns were similar to those found before implementation in both clinicians [20][21][22][23] and patients [6,7,9,12,[24][25][26][27]. However, all outcome measures in these studies were assessed subjectively, with the exception of Ross and Lin [21], who found that the number of messages from the patient to the doctor increased by 31% after the implementation of shared notes.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Access to medical notes (usually referred to as OpenNotes in the literature) through patient portals was another component of several studies. A study found that almost all patients described enhanced comprehension about their disease and care because of access to clinicians' notes, as the notes refreshed their memory and clarified their understanding of visits [74].…”
Section: Medical Notesmentioning
confidence: 99%
“…Patients reported that the medical notes eased their uncertainty, relieved anxiety, and facilitated control [74]. Denneson et al [75] found that reading OpenNotes helped 49% of patients have feelings ranging from very to extremely in control of their health care.…”
Section: Medical Notesmentioning
confidence: 99%
See 1 more Smart Citation